Creating a situation of success in the conditions of NUS (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the results of the analysis of thepsychological and pedagogical aspects of formatting the situation of success inthe educational process. The essence of the situation of success is revealed asone of the methods of organizing children's activities. The relevance andsignificance of the motivation for success in the process of teaching youngerschoolchildren in the NUS conditions is noted. The author emphasizes thatstudents experience success in learning is an important resource for the child’spersonal development. The author presents the results of an empirical study ofthe motivation for the success of schoolchildren. The conclusion is made aboutthe need to systematically create a situation of success for younger students inthe educational process.
Keywords: success, success situation, success motivation, junior schoolchild, New Ukrainian School